2005
DOI: 10.1071/he05005
|View full text |Cite
|
Sign up to set email alerts
|

The injury iceberg: an ecological approach to planning sustainable community safety interventions

Abstract: To reduce a community's risk of injury and sustain this lowered risk, the community 'ecological system' must have access to the resources necessary to maintain the desired outcome and the ability to mobilise these resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 24 publications
1
59
0
Order By: Relevance
“…Contrastingly, the capacity building paradigm proposes that sustainable social systems depend on the internal capacity of the system to remain productive. Many authors question whether this is realistic, given that administrative control over the necessary resources is often retained by agencies external to the target community (Hanson et al, 2005;La Fond, 1995;Nilsen et al, 2005;Olsen, 1998;Stefanini & Ruck, 1992;Swerissen & Crisp, 2004).…”
Section: Sustainable Injury Control and Safety Promotionmentioning
confidence: 98%
See 3 more Smart Citations
“…Contrastingly, the capacity building paradigm proposes that sustainable social systems depend on the internal capacity of the system to remain productive. Many authors question whether this is realistic, given that administrative control over the necessary resources is often retained by agencies external to the target community (Hanson et al, 2005;La Fond, 1995;Nilsen et al, 2005;Olsen, 1998;Stefanini & Ruck, 1992;Swerissen & Crisp, 2004).…”
Section: Sustainable Injury Control and Safety Promotionmentioning
confidence: 98%
“…McMurray (1999) suggests, 'A community can be viewed as an ecosystem, with resources, opportunities and threats to health and healthy lifestyles'. In this paradigm, a community must be understood in the context of its environment (Hanson et al, 2005;McMurray, 1999). The sustainability of the coalition is not only determined by its internal attributes, but also by its ability to productively interact with its external environment (Brinkerhoff & Goldsmith, 1992;Brush, 1975;Nilsen et al, 2005;Sciubba, 1995;von Bertalanffy, 1950).…”
Section: Sustainable Injury Control and Safety Promotionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, it has been found that up to 50% of community initiatives on safety have not been sustained (Hanson et al 2005). The aim of this study was to develop a framework enabling verification of the quality of community-based safety-promotion programmes in the global context.…”
Section: Introductionmentioning
confidence: 99%